Using Education Technology to Support Students with Special Educational Needs and Disabilities in Low- and Middle-Income Countries - Coflan, Caitlin Moss; Kaye, Thomas (EdTech Hub, 2020)
This brief focuses on how policymakers can make decisions about EdTech to support learners with special educational needs and/or disabilities (SEND) while offering policymakers the rationale and tools to move towards an inclusive approach. It also includes a detailed annex with descriptions, costs, availability, and examples of accessible and assistive technologies.
ZenodoArchiveID: 3744581 previousshortDOI: 10/ghgng7 previousDOI: 10.5281/zenodo.3744581 EdTechHub.Source: 2405685:2WY8H4WW EdTechHub.Source: <this> shortDOI: 10/ghgng7 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3744581 10.5281/zenodo.3744581 10.53832/edtechhub.0021 10/ghgng7 2129771:QEIBUIQH 2339240:3NRFPYGI 2339240:TK94XQR9 2339240:XJRI6FW3 2339240:Y635S3D4 2339240:Z7XXM8CG 2339240:ZZ8ISXSK 2405685:2WY8H4WW 2405685:6FFSC2Z8 2405685:DI4SGTPH 2405685:FLHI5BHC 2405685:FVE6PDBB 2405685:GG9HHSDL 2405685:PXAIRTEK 2405685:RLBPSG29
Keywords: F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-dode

A model of distance special education support services amidst COVID-19 - Frederick, Janice; Raabe, Ginger; Rogers, Valerie; Pizzica, Jessica (Behavioural Analysis in Practice, 2020)
The COVID-19 pandemic has significantly impacted the everyday life of many individuals across the globe. The school closures across the majority of the United States have presented administrators, educators, and behavior analysts with the unprecedented task of deciding how best to teach and support our students, especially those accessing special education services. The current paper describes the steps our program took, in light of school closures, to advocate for and ultimately create and implement a model that allows special education students to access the behavior analytic educational supports they had received on campus (e.g., BCBA and paraprofessional support) in a novel and remote manner. We share details regarding the advocacy and collaboration process as well as the distance special education support model itself in hopes that similar processes and models can be implemented across geographical locations to assist special education students in accessing their educational and behavioral supports in a meaningful way throughout current and future school closures.
Publisher: Behavior Analysis in Practice KerkoCite.ItemAlsoKnownAs: 10.31234/osf.io/q362v 2405685:I96LI4KA
Keywords: Applied behavior analysis; California Department of; applied behavior analysis; california department of education; covid-19; nonpublic agency; special education

Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The Covid-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable during school closures. They are isolated at home and unable to access information as easily as when attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
ZenodoArchiveID: 5652129 previousZenodoArchiveID: 3891379 previousshortDOI: 10/ghgnfv previousDOI: 10.5281/zenodo.3891379 EdTechHub.Source: 2405685:LP4PGMNA shortDOI: 10/ghgnfv KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3891379 10.5281/zenodo.3891379 10.5281/zenodo.4348995 10.53832/edtechhub.0043 10/ghgnfv 2129771:3YH4WC8N 2129771:J35ZR45N 2339240:6VEXVUL7 2339240:CDU93LQU 2339240:CUSR6ZBJ 2339240:FS3CFIBL 2339240:N7RDGZGY 2339240:V229A7WT 2339240:Z4FHRC9L 2405685:4PAZ4ZQH 2405685:8WYASBE4 2405685:KL56SD42 2405685:LP4PGMNA 2405685:S2A2EQQC 2405685:WFMBLBBE 2405685:XIQ5CL9B 2405685:XJ42VUQG 2405685:YY4LI6EI
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Smart buys, great sales and special offers: cost-effective approaches to improve global learning - Lewin, Keith; Learning | 0; Learning | 0 (The Education and Development Forum (UKFIET), 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:4GZPTGRL 2405685:7CGSPQI6

Education Ministry creates special online study platform for SHS students (2020)
The Ministry for Education has launched a special online study platform for Senior High School students. Ever since Covid-19 halted school activities the Education Ministry together with the Ghana Education Service has stepped up efforts to help...
Library Catalog: www.ghanaweb.com KerkoCite.ItemAlsoKnownAs: 2405685:BM7HEL24

Pakistan Social & Living Standards Measurement Survey 2018–19 - Government of Pakistan. Pakistan Bureau of Statistics, Government of Pakistan; Ministry of Planning Development & Special Initiatives (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:BD7K9LQT
Keywords: auto_merged

Kenya Institute of Special Education (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:FH3RYNEC

Inclusive considerations for optimal online learning in times of disasters and crises - Thompson, Kim M; Copeland, Clayton (Information and Learning Science, 2020)
Purpose: Special submission format guidelines indicate to insert placeholder and upload full abstract. Design/methodology/approach: Special submission format guidelines indicate to insert placeholder and upload full abstract. Findings: Special submission format guidelines indicate to insert placeholder and upload full abstract. Research limitations/implications: Special submission format guidelines indicate to insert placeholder and upload full abstract. Practical implications: Special submission format guidelines indicate to insert placeholder and upload full abstract. Social implications: Special submission format guidelines indicate to insert placeholder and upload full abstract. Originality/value: Special submission format guidelines indicate to insert placeholder and upload full abstract.
KerkoCite.ItemAlsoKnownAs: 10.1108/ILS-04-2020-0083 2405685:348CQHBQ
Keywords: Course design; Diversity; Equity; Evidence-based practice; Inclusion; Inclusive pedagogy; Learning environment; Universal design for learning; pedagogy

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
previousDOI: ​10.5281/zenodo.4299931 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4299931 10.5281/zenodo.4768560 2339240:CYPLQHH4 2405685:C49UMTX2 2405685:CWRFU9K9
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

EdTech and the COVID-19 response: A case study of Kenya - Ngware, Moses; Ochieng, Vollan (EdTech Hub, 2020)
ZenodoArchiveID: 4706019 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706019 2339240:D85SY35R 2405685:SMLIMS2X
Keywords: Kenya; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:35E4A2TD 2339240:4LGNB3A8 2339240:AA5FSXJC 2339240:RYJUP2SP 2405685:ATRDA7GD 2405685:BYEPNBQB 2405685:CLFVRHB5 2405685:EIZKB3Q4 2405685:QCXEVZTI 2405685:VMYU87NN 2405685:WWNJCJVG 2405685:ZFJGNIZJ 4656463:7UTAZK7R
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Appraising research on personalized learning: definitions, theoretical alignment, advancements, and future directions - Walkington, Candace; Bernacki, Matthew L. (Journal of Research on Technology in Education, 2020)
This article introduces a special issue comprising research on efforts to personalize learning in different academic subjects. We first consider the emergence of personalized learning (PL) and the myriad of definitions that describe its essential features. Thereafter, we introduce the articles in the special issue by examining their alignment to extant theories of learning, the instructional design features that personalize the learning experience based on a learner characteristic, and the relationships between PL design and outcomes achieved in an educational context. Based on observations of contemporary PL research, we identify key issues to be addressed by the field and recommendations for future researchers to undertake to advance a PL theory. Chief among issues with PL are the role of technology, the agency of the learner, and the absence of a consistent theoretical grounding to motivate PL design choices. Future directions that would advance PL include the adoption of a theory of change in PL design, a design-based research approach to refine PL initiatives, more intensive and iterative research in authentic classroom contexts, and a greater focus on student input into and ownership of the PL experience.
KerkoCite.ItemAlsoKnownAs: 10.1080/15391523.2020.1747757 2339240:DUK6NXYD 2405685:WF9TK4TD

Promoting physical activity for children with autism spectrum disorders during Coronavirus outbreak: Benefits, strategies, and examples - Yarımkaya, Erkan; Esentürk, Oğuz Kaan (International Journal of Developmental Disabilities, 2020)
Described as a global outbreak (pandemic) by the World Health Organization, Coronavirus disease (COVID-19) raises great concern with more than 2 million infected patients worldwide. A series of measures are taken by governments worldwide to prevent the spread of the outbreak. As new cases increase, people are asked to stay at home. Active living areas such as sports centers, parks and schools are closed in most countries. In this process, staying at home for a long time makes it difficult for individuals with special needs such as Autism Spectrum Disorders (ASD) to stay physically active as well as typically developing individuals. The education process of children with ASD is disrupted, especially due to closed special education schools and rehabilitation centers. Online learning environments are often not suitable for children with ASD. It is predicted that excessive weight, obesity and sedentary life, which are high in children with ASD, may increase even more due to COVID-19. This article outlines the benefits of physical activity for children with ASD and provides strategies and examples of physical activity for children with ASD during the COVID-19 outbreak. The article is thought to be a guide for encouraging children with ASD in the home environment to physical activity.
KerkoCite.ItemAlsoKnownAs: 10.1080/20473869.2020.1756115 2405685:4SKEKBD6
Keywords: COVID-19; children with ASD; physical activity; stay at home

What steps are being taken to reach the most disadvantaged students during the period of Covid-19 school closure? - McAleavy, Tony; Joynes, Chris; Gibbs, Emma; Sims, Kate (Education Development Trust, 2020)
ZenodoArchiveID: 4705909 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705909 2339240:7ZRTPCRD 2339240:QN533HVR 2339240:SU542298 2405685:2HZ9V7IF 2405685:4CKXCNC2 2405685:9JB5M3HI 2405685:BAEUEWI9 2405685:CY5UL3B9 2405685:E3GHWHIZ 2405685:WXF7VILV
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Education technology in the COVID-19 response in Pakistan - Tabassum, Rabia; Hadi, Murium; Qaisrani, Ayesha; Shah, Qasim (EdTech Hub, 2020)
ZenodoArchiveID: 4705912 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705912 2339240:26FUGGA3 2339240:X339ME8R 2405685:EHKCNED4 2405685:NIVS5RZF 2405685:TWMVIX77
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Guidance Note 4 Inclusion and accessible learning for people with disabilities From the Report: Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (UNESCO, UniTwin, EdTech Hub, 2020)
ZenodoArchiveID: 4684317 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684317 2339240:LKN74WQK 2405685:56QA2K9Y
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Education technology in the COVID-19 response in Nigeria - Isisi, Akogun; Olojede, Omolola; Adedoyin, Adesina; Akogun, Oladele (EdTech Hub, 2020)
ZenodoArchiveID: 4706031 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706031 2339240:LNRXZMBD 2405685:RG93WYZD
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Distance learning in the context of COVID-19: the case of Rwanda - Ngabonzima, Ernest; Isimbi, Roberte; Mwali, Marie Merci; Pellini, Arnaldo (EdTech Hub, 2020)
ZenodoArchiveID: 4706016 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706016 2339240:F62THLX3 2339240:V5PQVKX2 2405685:ADNJFTFA 2405685:CMDUS73G 2405685:T2JBHFBC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Building effective COVID-19 Education Response Plans: Insights from Africa and Asia - Kimenyi, Eric; Otieno, Jennifer; Kaye, Tom (EdTech Hub, 2020)
previousshortDOI: 10/ghgk6r previousDOI: 10.5281/zenodo.3884302 EdTechHub.Source: 2405685:6W2UWE89 EdTechHub.Source: <this> shortDOI: 10/ghgk6r KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3884302 10.53832/edtechhub.0041 10/ghgk6r 2129771:2MD2QL8K 2339240:7QEJ68RG 2405685:6W2UWE89 2405685:7HQN2HAD
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Accessibility - Wikipedia (Wikipedia, 2020)
Accessibility in the sense considered here refers to the design of products, devices, services, or environments so as to be usable by people with disabilities. The concept of accessible design and practice of accessible development ensures both "direct access" (i.e. unassisted) and "indirect access" meaning compatibility with a person's assistive technology (for example, computer screen readers). Accessibility can be viewed as the "ability to access" and benefit from some system or entity. The concept focuses on enabling access for people with disabilities, or special needs, or enabling access through the use of assistive technology; however, research and development in accessibility brings benefits to everyone.Accessibility is not to be confused with usability, which is the extent to which a product (such as a device, service, or environment) can be used by specified users to achieve specified goals with effectiveness, efficiency, convenience satisfaction in a specified context of use.Accessibility is strongly related to universal design which is the process of creating products that are usable by people with the widest possible range of abilities, operating within the widest possible range of situations. This is about making things accessible to all people (whether they have a disability or not).
Page Version ID: 984895511 KerkoCite.ItemAlsoKnownAs: 2405685:UQE9CKPF

Trends in educational research about e-learning: a systematic literature review (2009–2018) - Valverde-Berrocoso, Jesús; Garrido-Arroyo, María del Carmen; Burgos-Videla, Carmen; Morales-Cevallos, María Belén (Sustainability, 2020)
The concept of e-learning is a technology-mediated learning approach of great potential from the educational perspective and it has been one of the main research lines of Educational Technology in the last decades. The aim of the present systematic literature review (SLR) was to identify (a) the research topics; (b) the most relevant theories; (c) the most researched modalities; and (d) the research methodologies used. To this end, the PRISMA protocol was followed, and diﬀerent tools were used for the bibliographic management and text-mining. The literature selection was carried out in three ﬁrst-quartile journals indexed in JCR-SSCI specialized in Educational Technology. A total of 248 articles composed the ﬁnal sample. The analysis of the texts identiﬁed three main nodes: (a) online students; (b) online teachers; and (c) curriculum-interactive learning environments. It was revealed that MOOC was the most researched e-learning modality. The Community of Inquiry and the Technological Acceptance Model, were the most used theories in the analyzed studies. The most frequent methodology was case study. Finally, the conclusions regarding the objectives of our SRL are presented: Main themes and research sub-themes, most researched e-learning modality, most relevant theoretical frameworks on e-learning, and typologies of research methodologies.
KerkoCite.ItemAlsoKnownAs: 10.3390/su12125153 10/ghvnfd 2339240:CMZ8HVYI 2405685:EWKSK6YI

Ghana’s education response during the COVID-19 crisis: EdTech to the rescue? - Agbe, Edem; Sefa-Nyarko, Clement (EdTech Hub, 2020)
ZenodoArchiveID: 4706036 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706036 2339240:CB8D4LUQ 2339240:METE88UD 2339240:MK55NVDC 2339240:Z3EF9Q75 2405685:3XIBJD8G 2405685:3Y33YNL3 2405685:8JZVGC6W 2405685:HBXKVKMA 2405685:QJ783WH5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH

An inclusive approach to searching for evidence on EdTech in low- and middle- income countries - Brugha, Meaghan (EdTech Hub, 2020)
A blog post by Meaghan Brugha and Katy Jordan. A searchable database The EdTech Hub has undertaken a large-scale search for publications on technology use in education in low- and middle- income countries. During this process, we created an internal research database. This is searchable through the use of a variety of filters, such as …
EdTechHub.Source: <this> EdTechHub.Source: 2405685:BGLPB3AG KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3911079 2129771:86J5A5RJ 2405685:6TX2RFBC 2405685:BGLPB3AG
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoODE

Remote eye-tracking for cognitive telerehabilitation and interactive school tasks in times of COVID-19 - Iannizzotto, Giancarlo; Nucita, Andrea; Fabio, Rosa Angela; Caprì, Tindara; Bello, Lucia Lo (Information (Switzerland), 2020)
In the attempt to mitigate the effects of COVID-19 lockdown, most countries have recently authorized and promoted the adoption of e-learning and remote teaching technologies, often with the support of teleconferencing platforms. Unfortunately, not all students can benefit from the adoption of such a surrogate of their usual school. We were asked to devise a way to allow a community of children affected by the Rett genetic syndrome, and thus unable to communicate verbally, in writing or by gestures, to actively participate in remote rehabilitation and special education sessions by exploiting eye-gaze tracking. As not all subjects can access commercial eye-tracking devices, we investigated new ways to facilitate the access to eye gaze-based interaction for this specific case. The adopted communication platform is a videoconferencing software, so all we had at our disposal was a live video stream of the child. As a solution to the problem, we developed a software (named SWYG) that only runs at the "operator" side of the communication, at the side of the videoconferencing software, and does not require to install other software in the child's computer. The preliminary results obtained are very promising and the software is ready to be deployed on a larger base. While this paper is being written, several children are finally able to communicate with their caregivers from home, without relying on expensive and cumbersome devices.
KerkoCite.ItemAlsoKnownAs: 10.3390/info11060296 2405685:8EIPHM8H
Keywords: COVID-19; Remote interactive education; Telerehabilitation; Video conferencing; Video-based eye-gaze tracking

Rolling Out a National Virtual Learning Environment - Adam, Taskeen; McBurnie, Chris; Haßler, Björn (EdTech Hub, 2020)
A virtual learning environment (VLE) is a virtual space designed to support teaching and learning and can resemble anything from a curated content repository to a synchronous video-enabled learning space. This technical note aims to inform the design and implementation of a VLE at a national level for basic education.
previousshortDOI: 10/ghgnf6 previousshortDOI: 10/ghgnf6 previousDOI: 10.5281/zenodo.3406132 previousshortDOI: 10/ghgnf6 EdTechHub.Source: 2405685:KWJRW62J EdTechHub.Source: <this> shortDOI: 10/ghgnf6 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3406132 10.5281/zenodo.3406132EdTechHub.ItemAlsoKnownAs: 10.53832/edtechhub.0010 10/ghgnf6 2129771:3H8JIJ9T 2129771:MG4TM5B3 2339240:CN8LY32H 2339240:EG4V9NYX 2339240:T37Q6QE6 2339240:W2B4DTPS 2405685:7EP4VHD7 2405685:B76WDWTE 2405685:KWJRW62J 2405685:QFMSIUXQ 2405685:Y4EVL7PR 2486141:TAPS8LVP
Keywords: F: Helpdesk response; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Indian educators' awareness and attitude towards assistive technology - Kundu; Bej, Tripti (Journal of Enabling Technologies, 2020)
Objective: This study investigated the awareness and attitude of Indian mainstream secondary school teachers on assistive technologies (AT) and its implementation level in inclusive setting. Methodology: The study followed descriptive survey method within ex-post-facto research design taking 150 teachers including 15 headmasters from 15 secondary schools as samples following stratified random sampling technique. Questionnaires and interviews (according to set interview protocol) were the main research tools used during survey. Collected data were analyzed descriptively and inferentially to reach a conclusion. Findings: Findings revealed that Indian mainstream secondary school teachers’ awareness of AT was very poor yet their attitude towards it was highly positive. Except having a good attitude, everywhere- the teachers’ knowledge, professional support, or infrastructural support- the inadequacy was obvious. Indian schools were running with a poor resource pool of assistive products along with poor implementation. Hence special need students of these schools were not getting the necessary supports from schools as they deserve which has been hampering the overall inclusive atmosphere of the country. Statistical analysis revealed that male teachers showed slightly higher awareness level regarding AT than their female counterparts but in respect of attitude they were found overpowered by the females. Teachers of urban schools also exhibited slightly better awareness and attitude towards AT than the teachers of rural schools. Lack of suitable policies, adequate awareness and financial limitations were evolved as major barriers in the implementation of AT in these schools.
KerkoCite.ItemAlsoKnownAs: 10.1108/JET-04-2020-0015 2339240:4L9AFNDX 2405685:3SG4D2ZC

Why the World Needs a Curriculum Alignment Hub - Chandra, Shivi (Learning Equality, 2020)
ZenodoArchiveID: 5534235 previousDOI: 10.5281/zenodo.4314923 previousDOI: 10.5281/zenodo.4768580 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4314923 10.5281/zenodo.4768580 10.53832/edtechhub.0046 2339240:XFMP94YR 2405685:2RMKAHXF 2405685:TLNPJ4IA 2405685:ZNQYTUVV
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; _zenodoETH:submitted

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:X5MR76ZW 2405685:29U93GQF

EdTech in Ghana: A Rapid Scan - Taddese, A. (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. These factors include the policy or vision for EdTech, institutional capacity, private sector partnerships, and digital infrastructure. The scans are intended to be comprehensive but are by no means exhaustive; however, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and, in this case, Ghana. This report is based primarily on desk research, with quality assurance provided by a country expert.
previousshortDOI: 10/ghgk65 previousDOI: 10.5281/zenodo.3830951 shortDOI: 10/ghgk65 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3830951 10.5281/zenodo.3830951 10.53832/edtechhub.0030 10/ghgk65 2339240:2AU72ZG2 2339240:3DWURGVT 2339240:KMTF4A22 2339240:L86PMYJ2 2339240:PRSHWWK5 2405685:4TKSDH2I 2405685:97JHVZU9 2405685:GUJ3TBS3 2405685:NA8X7J9C 2405685:S3EKNHHG 2405685:XGAFJNAD 4656463:PU6FSTAF
Keywords: Access; C:Ghana; Distance learning; EdTech; LP: English; Online learning; Remote learning; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodoETH

What are countries doing that already use remote learning extensively? What can we learn from them? - Ndaruhutse, Susy; Gibbs, Emma; Fitzpatrick, Rachael (2020)
ZenodoArchiveID: 4706067 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706067 2339240:Y24AUHV8 2405685:I3AV65H3 2405685:WQ8HX957
Keywords: H: Distance education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
ZenodoArchiveID: 4768571 previousDOI: 10.5281/zenodo.4277895 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4277895 10.5281/zenodo.4768571 2339240:5M4KPPAH 2339240:MQLLLDAJ 2405685:S7JARBXV 2405685:T2HBLDU6 2405685:TE7A3D6X
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
ZenodoArchiveID: 3865298 previousshortDOI: 10/ghgk6p previousshortDOI: 10/ghgk6p previousDOI: 10.5281/zenodo.3865298 shortDOI: 10/ghgk6p KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3865298 10.53832/edtechhub.0020 10/ghgk6p 2129771:2BEHBMUH 2129771:C6TREICJ 2129771:GQ4U9R5Z 2129771:QFFBWT4D 2339240:H8RZC7AY 2339240:T5DE93E2 2405685:3HP24UTI 2405685:CEADG684 2405685:H52W8E9M 2405685:HFKVA2IQ 2405685:U2AQUAZ2 2486141:B8P7D4EU
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

India’s distance learning response to the COVID-19 crisis - Doraiswamy, Harish; Gupta, Gouri; Kamath, Dhruv; Sharma, Sudhanshu (Central Square Foundation, EdTech Hub, 2020)
ZenodoArchiveID: 4705451 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705451 2339240:CMSHWXFV 2339240:QDQHFQXB 2405685:2HFSJ78U 2405685:YEQSJBYT
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Continue or reboot? Overarching options for education responses to COVID-19 in low- and middle-income countries - Haßler, Björn (2020)
Björn Haßler, https://opendeved.net/2020/04/15/continue-or-reboot/, 2020-04-15, DOI: 10.5281/zenodo.3753513
EdTechHub.Source: 2129771:MIMJJLN9 shortDOI: 10/ghgk6t KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3753513 10.5281/zenodo.4706085 10/ghgk6t 2129771:AS5ALSKL 2129771:MIMJJLN9 2339240:742PGZ2D 2405685:36KIX7YE 2405685:5IMAIVQY 2405685:696M6DK9 2405685:RAAGIU4Q
Keywords: COV:COVID and reopening of schools; LP: English; _DOILIVE; _EdTechHub_Output; _yl:p; _zenodoETH; _zenodoODE; dode_eth-src-dode; dode_eth-trf2-dode

China: testing a decade of online education preparation - Liangdi, Xu; Groenewegen-Lau, Jeroen (EdTech Hub, 2020)
ZenodoArchiveID: 4705990 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705990 2339240:S2B995E4 2405685:P5B4YWID
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

COVID-19 and the education response in Indonesia: exploring the learning crisis - Suriastini, Wayan; Setyo, Pujiastuti; Herawati, Fita; Naryanta; Moddilani, Ganiko; Pellini, Arnaldo (EdTech Hub, 2020)
ZenodoArchiveID: 4705994 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4705994 2339240:FMIXJN4W 2405685:VZ3IMPYX
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v2; _zenodo:submitted; _zenodoETH

Overview of emerging country-level response to providing educational continuity under COVID-19: What are the lessons learned from supporting education for marginalised girls that could be relevant for EdTech responses to COVID-19 in lower- and middle-income countries? - Naylor, Ruth; Gorgen, Kristine (EdTech Hub, 2020)
ZenodoArchiveID: 4706059 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4706059 2339240:3HJRFVNR 2339240:3VR6UC7F 2339240:9U79NYYD 2339240:NCZSLKX5 2339240:UEWQXHSF 2339240:YFCV9UXA 2339240:YMYNESML 2405685:9NJI87R8 2405685:B54L7JGC 2405685:C6QUC3Z7 2405685:D9SU8CEK 2405685:LK4JMG78 2405685:PW66MNDR 2405685:SLJSKY8J 2405685:VSAZQYD7 2405685:Z3XYMJZN
Keywords: COV:COVID and reopening of schools; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Accelerated Learning and EdTech: A Rapid Evidence Review - Damani, Kalifa (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of accelerated learning in low- and middle-income countries (LMICs), with a focus on how EdTech might best be utilised for accelerated learning. It begins with a broad discussion of the components of accelerated learning, followed by a more focused discussion on how accelerated learning has been used to enhance learning outcomes for marginalised groups in LMICs. An exploration of how EdTech can be utilised for accelerated learning is then presented.
ZenodoArchiveID: 4556941 Note: This item replaced a previous version with DOI 10.5281/zenodo.4071441. PreviousDOI: 10.5281/zenodo.4071441 PreviousDOI: 10.5281/zenodo.4477135 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4556941 10.5281/zenodo.4071441 10.5281/zenodo.4477135 10.5281/zenodo.4556941 2339240:785U4JZJ 2339240:9MZRHWYE 2339240:TQLWMAIZ 2405685:9BWHLEWZ 2405685:I4UFGAQA 2405685:JV5JCGN3 2405685:XNYSHYYD
Keywords: L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v2; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

What can be learnt from China’s recent experiences with Covid-19 and school closures that can inform other countries’ education technology-enabled responses? - Hallgarten, Joe; Fitzpatrick, Rachael (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:FY4BHGH3

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
ZenodoArchiveID: 4556932 PreviousDOI: 10.5281/zenodo.4477141 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3948149 10.5281/ZENODO.4556932 10.5281/zenodo.4477141 10.5281/zenodo.4556932 2259720:DSXFK6JB 2339240:4JRWSL6I 2339240:8YVF7D5N 2339240:EPCMUN8C 2339240:FKFII8IK 2339240:H8YNQIY9 2339240:IJJ6TY76 2339240:QBDJ6U43 2339240:YIAFCN9T 2405685:5GBRDVHP 2405685:65UPSCK3 2405685:67BFM4C5 2405685:6CG6479A 2405685:DM6JSS9K 2405685:P8NUYK3M 2405685:PZHGV2XR 2405685:QBYZW7N2 2405685:RBUXXHAD 2405685:VHGNZV9N 2405685:X8BFH2K5 2405685:YMWE6FR6
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
previousshortDOI: 10/ghgng8 previousDOI: 10.5281/zenodo.3874247 EdTechHub.Source: 2405685:VX7UW757 EdTechHub.Source: <this> 2339240:KPL424XH shortDOI: 10/ghgng8 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3874247 10.5281/zenodo.3874247 10.53832/edtechhub.0025 10/ghgng8 2129771:LBII97HZ 2339240:2R8Z34D2 2339240:FT2TLP7Q 2339240:G93JLKST 2339240:J7DSQVEZ 2339240:QSKUJUNV 2339240:YK2KWXPL 2405685:2D6GK36K 2405685:48AAKD33 2405685:7VFMN2XM 2405685:G7ZB68PJ 2405685:I5WKHBZI 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA 2405685:ZUDWQVKI
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
ZenodoArchiveID: 4749652 previousDOI: 10.5281/zenodo.4018774 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4749652 2339240:B796SJQD 2339240:DI5RWJ4S 2405685:6MJNV8GC 2405685:TFLZLVTW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
ZenodoArchiveID: 4556938 PreviousDOI: 10.5281/zenodo.4058181 PreviousDOI: 10.5281/zenodo.4477015 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4058181 10.5281/ZENODO.4556938 10.5281/zenodo.4477015 10.5281/zenodo.4556938 2339240:8QFLYEYK 2339240:ATYZFQ8R 2339240:CUBEJEWS 2339240:LCAUL9ZC 2339240:NISQD6JT 2339240:T2Z992XW 2339240:XMQV9Y56 2339240:YGQCMSDP 2405685:2GE8ESCR 2405685:4G8DT7ZB 2405685:4JM6QWPH 2405685:5NMCR3LL 2405685:EQVI8NMV 2405685:IU849P3E 2405685:MMTHETFR 2405685:PY3CXCH9 2405685:QSD5LYSF 2405685:XHBPFYVC 2405685:Z7P9NRWJ
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
ZenodoArchiveID: 5652092 previousDOI: 10.5281/zenodo.4140104 previousZenodoArchiveID: 4140104 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4140104 10.5281/zenodo.4140104 10.5281/zenodo.4140104; 10.5281/zenodo.5652092 2339240:2K6FG2CF 2339240:2XJTN3MP 2339240:3TNWACL9 2339240:942WVA7N 2339240:DN7NQV5Y 2339240:LKQW3A8S 2339240:MDTPARWA 2339240:PNTVB7PY 2339240:U3838PXA 2339240:XIE9NJ3S 2405685:5DNJGPNU 2405685:BA3K6CK8 2405685:BLRKEEAU 2405685:CCZW4ARW 2405685:DAFBBJ3F 2405685:DP9HJGLT 2405685:HRT8E6US 2405685:RVIEHPP5 2405685:XUVA9827 2405685:Z6UIK8CZ 2405685:ZITF5IDK 2534379:FDZIF5DH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
previousshortDOI: 10/gg8hqq previousshortDOI: 10/gg8hqq previousDOI: 10.5281/zenodo.3804380 previousshortDOI: 10/gg8hqq EdTechHub.Source: 2405685:UXQG7GRG EdTechHub.Source: <this> shortDOI: 10/gg8hqq KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3804380 10.53832/edtechhub.0014 10/gg8hqq 2129771:X82WTVD8 2339240:4X8SH6RY 2339240:MB7JNNNV 2339240:PGI4RZNE 2405685:59LAMBXS 2405685:88UWQMW9 2405685:BG5DGC4G 2405685:GQDN2E5P 2405685:SYLGY9MM 2405685:UXQG7GRG
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2405685:MWNVG7LR
Keywords: auto_merged

Remote Learning: Rapid Evidence Assessment - Education Endowment Foundation (Education Endowment Foundation, 2020)
This rapid evidence assessment aimed to investigate methods that schools could use to support remote learning during school closures caused by the 2020 coronavirus pandemic (Covid-19). The review sought to find the best evidence behind the wide array of approaches that schools might choose to use during the crisis. The review systematically searched for/through existing meta-analyses and systematic reviews to find the best evidence for a wide range of approaches. In addition to the direct teaching of pupils online by teachers, the review also found evidence for approaches that pupils can use independently, including with technology that adapts the content of tasks in order to provide additional challenge or support, educational games, and for approaches that support peer interaction. The review also examined blended learning approaches, which combine remote and classroom teaching. While these approaches may not be directly applicable during school closures, they were included in case there were useful lessons to be learned that were relevant to the current context of home learning. This report summarises the findings from 60 systematic reviews and meta-analyses answers under five key topic areas: - General remote teaching and learning - Blended learning - Computer-supported collaborative learning - Computer assisted instruction - Educational games Another crucial aspect of supporting pupil’s learning is parental engagement. Parental engagement approaches are beyond the scope of this review, but an existing EEF guidance report, Working with Parents to Support Children’s Learning (2019), and accompanying evidence review summarise the best available evidence for engaging parents in their children’s education. In each section, we have detailed the included reviews and listed Findings and implications drawn from the evidence. We have also highlighted case studies from projects funded by the Education Endowment Foundation in which similar approaches have been rigorously evaluated in English schools.
ZenodoArchiveID: 4477023 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4477023 2259720:VZ7YJUFN 2339240:85V26WNW 2339240:HGMUANP7 2339240:JIW4TDS5 2339240:VJ8WRVRV 2405685:8ASGAE9Q 2405685:B3K7PU24 2405685:GPMMTF99 2405685:HCC97T3B 2405685:LW2NDPNQ 2405685:V3SZZR28
Keywords: Methods; _DOILIVE; _EdTechHub_Output; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Online and distance teaching and learning A32ARSFK; _cover:other:ok; _zenodo:submitted; _zenodoETH

Teacher professional development and coaching in low-income countries: Practical considerations for the use of technology. - Haßler, Björn (EdTech Hub, 2020)
This working paper forms part of a set of three working papers that consider teacher professional development and coaching in low-income countries. This third paper offers a range of practical considerations.
previousshortDOI: 10/ghgngk previousshortDOI: 10/ghgngk previousDOI: 10.5281/zenodo.3631750 previousshortDOI: 10/ghgngk EdTechHub.Copy: 2129771:5EWDQDIA EdTechHub.ThisIsNot: 2339240:94ZP3EK4 shortDOI: 10/ghgngk KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3631750 10.53832/edtechhub.0013 10/ghgngk 2129771:5EWDQDIA 2339240:4KQKED7R 2339240:94ZP3EK4 2405685:978RP7D4 2405685:VM6NXYF3
Keywords: E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _yl:o; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Deploying an e-Learning Environment in Zanzibar: Feasibility Assessment - Groeneveld, Caspar; Kibga, Elia; Kaye, Tom (EdTech Hub, 2020)
The Zanzibar Ministry of Education and Vocational Training (MoEVT) and the World Bank (the Bank) approached the EdTech Hub (the Hub) in April 2020 to explore the feasibility of implementing a Virtual Learning Environment (VLE). The Hub was requested to focus primarily on the deployment of a VLE in lower secondary education, and this report consequently focuses primarily on this group. The report is structured in four sections: An introduction to provide the background and guiding principles for the engagement with a short overview of the methodology applied. An analysis of the Zanzibar education system with a particular focus on elements relevant to deploying a VLE. This includes the status of ICT infrastructure, and a summary of the stakeholders who will play a role in using or implementing a VLE. A third section that discusses types of VLEs and content organisation, and their applicability to the Zanzibar ecosystem. A conclusion with recommendations for Zanzibar, including short- and long-term steps. In this collaboration with Zanzibar’s MoEVT, the Hub team sought to understand the purpose of the proposed VLE. Based on discussions and user scenarios, we identified two main education challenges a VLE may help to resolve. In the short term, students cannot go to school during the COVID-19 crisis, but need access to educational content. There is content, but no flexible and versatile platform to disseminate content to all students. In the long term, a mechanism to provide students with access to quality, curriculum-aligned content in school, or remotely, is required.
ZenodoArchiveID: 5652121 previousZenodoArchiveID: 3941727 previousDOI: 10.5281/zenodo.3941727 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3941727 10.53832/edtechhub.0028 2129771:KLLMDHKK 2339240:Y5Z46TRU 2405685:2B8SH5S3 2405685:K7JDL4IL
Keywords: C:Tanzania; H:Online learning; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (Education Commission, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
shortDOI: 10/ghgk64 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3983877 10/ghgk64 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:7SUZMICK 2339240:BGZYE7EH 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:88MADQ2R 2405685:FPPVW2ZG 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6 2405685:WVC3S4C8
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
shortDOI: 10/ghgk63 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4118177 10/ghgk63 2129771:NXT72X66 2129771:RZZI4WU9 2129771:XY56AEY8 2339240:BGZYE7EH 2339240:FTULJL3H 2339240:Q3INH4WN 2339240:V2JUHPPN 2405685:2G7TFTEB 2405685:F2B8T3ZP 2405685:GI3IBRKA 2405685:IA9PL99D 2405685:P84UGFG8 2405685:SXDQAPB6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Refugee Education: A Rapid Evidence Review - Ashlee, Amy; Clericetti, Giulia; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for education of refugees in low- and middle-income countries (LMICs). The RER has been produced in response to the widespread global shutdown of schools resulting from the outbreak of Covid-19. It therefore has an emphasis on transferable insights that may be applicable to educational responses resulting from the limitations caused by Covid-19. In the current global context, lessons learnt from the use of EdTech in refugee contexts — in which education is often significantly disrupted and education systems and responses are required to rapidly adapt — are salient.
ZenodoArchiveID: 4557019 PreviousDOI: 10.5281/zenodo.4477154 PreviousShortDOI: 10/ghgnf2 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3901521 10.5281/zenodo.4557019 10/ghgnf2 2339240:3KCTC7UA 2339240:5B7T9LEG 2339240:K45TP2GI 2339240:NNZ9DD54 2339240:SIV6ZELZ 2339240:W3ALIEA9 2405685:397HVPFN 2405685:4M9GTG8I 2405685:5AWZGNCG 2405685:6EUNRYPS 2405685:E56IKGK2 2405685:E6DMTNLL 2405685:TXGBLY4U 2405685:UUNEJ7FS 2405685:W9JLL7JV
Keywords: L:Refugees and migrants; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _P:Evidence review VCMFM9ZD; _cover:v3; _zenodo:submitted; _zenodoETH

What does the research suggest is best practice in pedagogy for remote teaching? - McAleavy, Tony; Gorgen, Kristine (2020)
KerkoCite.ItemAlsoKnownAs: 2405685:89I7MWHD 2405685:XHIZKSIA
Keywords: ___working_potential_duplicate; ⛔ No DOI found

Child-directed Tablet-based Learning: Toolkits for project design, preparation, and implementation - Imagine Worldwide (2020)
KerkoCite.ItemAlsoKnownAs: 2339240:PNMXVDQ2 2405685:A4NNJNSJ 2405685:GBIY52AG

Education for the most marginalised post‑COVID-19: Guidance for governments on the use of digital technologies in education ACT TWO (OF THREE): FULL REPORT - Unwin, Tim; Naseem, Azra; Pawluczuk, Alicja; Shareef, Mohamed; Spiesberger, Paul; West, Paul; Yoo, Christopher (EdTech Hub, UNESCO, UniTwin, 2020)
ZenodoArchiveID: 4684361 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4684361 2339240:SL23268I 2339240:VTWI3GZJ 2405685:UF3XJXGS 2405685:UXHEIEWM 2405685:ZA9RWW28
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _zenodo:submitted; _zenodoETH

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
ZenodoArchiveID: 5652066 previousZenodoArchiveID: 3885606 previousshortDOI: 10/ghgnfw previousDOI: 10.5281/zenodo.3885606 EdTechHub.Copy: 2129771:VAP9K6BW EdTechHub.Copy: 2129771:VAP9K6BW shortDOI: 10/ghgnfw KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3885606 10.5281/zenodo.3885606 10.53832/edtechhub.0026 10/ghgnfw 2129771:IK97VLY8 2129771:MXTVUGAA 2129771:VAP9K6BW 2339240:2ZVLRPTQ 2339240:7PXTZ2FQ 2339240:ZE9V9N4R 2405685:8IJT433J 2405685:9TKV7H6E 2405685:BBLQFJKE 2405685:IDL75DHT 2405685:WMUEC2ZV 2405685:Z2VNN7ER
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

National Framework for Teachers Continuous Professional Development - Ministry of Education, Science and Technology (United Republic of Tanzania, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:PX8LX2HD 2405685:HWT67YS2 2405685:MUSAVHQ9

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
EdTechHub.Source: 2129771:WMYNLNVK KerkoCite.ItemAlsoKnownAs: 2129771:GIJXZ5UC 2129771:WMYNLNVK 2129771:ZQ6YQRSI 2405685:TI6VMAWR 2405685:TRRZUHFS 2486141:HFLTMIZV
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode

Overview of emerging country-level response to providing educational continuity under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
KerkoCite.ItemAlsoKnownAs: 2339240:5NZNS3QV 2339240:CPK8K89T 2339240:RBDWQM22 2405685:6RBRWKND 2405685:I9KB2AZ7 2405685:KV39KIGX 2405685:NVJN7R29 2405685:YD8GYZDT
Keywords: ⛔ No DOI found